2010
DOI: 10.3758/brm.42.2.474
|View full text |Cite
|
Sign up to set email alerts
|

Age-of-acquisition norms for a set of 1,749 Portuguese words

Abstract: In 1973, Carroll and White showed that words acquired earlier in life tend to be processed faster and more accurately than later acquired words in a picture naming task. From that moment on, age of acquisition (AoA) was considered to be a relevant psycholinguistic variable, and several experimental studies have replicated the effect found by Carroll and White in many paradigms (e.g., picture naming-Barry, Holmes & Ellis, 2006;Lambon Ralph & Ehsan, 2006; written-word naming-Brysbaert, Lange, & Van Wijnendaele,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
32
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 41 publications
7
32
0
2
Order By: Relevance
“…A review of 54 publications revealed that the majority of the subjective AoA studies did not state the exact form of the question at all Alario & Ferrand, 1999;Alonso, Fernandez, & Díez, 2015;Bakhtiar et al, 2013;Barry et al, 2006;Bird et al, 2001;Bonin, Boyer, Méot, Fayol, & Droit, 2004b;Bonin et al, 2003;Bonin, Perret, Méot, Ferrand, & Mermillod, 2008;Cameirão & Vicente, 2010;Cuetos et al, 1999;Cuetos et al, 2012;De Deyne & Storms, 2007;Della Rosa et al, 2010;Dimitropoulou et al, 2009;Johnston, Dent, Humphreys, & Barry, 2010;Lyons et al, 1978;Manoiloff et al, 2010;Marques, Fonseca, Morais, & Pinto, 2007;Moors et al, 2013;Moreno-Martínez et al, 2014;Nishimoto et al, 2005;Nishimoto, Ueda, Miyawaki, Une, & Takahashi, 2012;Raman et al, 2014;Schock, Cortese, Khanna, & Toppi, 2012;Schröder, Gemballa, Ruppin, & Wartenburger, 2011;Sirois et al, 2006;Stration et al, 1975;Tsaparina et al, 2011;Vinson et al, 2008;Walley & Metsala, 1992;Winters, Winter, & Burger, 1978). In the remaining articles, the wording BWhen do you think you learned this word?^is most frequently used (e.g., Auer & Bernstein, 2008;Barca et al, 2002).…”
Section: Methodological Aspects Of Aoa Studiesmentioning
confidence: 99%
“…A review of 54 publications revealed that the majority of the subjective AoA studies did not state the exact form of the question at all Alario & Ferrand, 1999;Alonso, Fernandez, & Díez, 2015;Bakhtiar et al, 2013;Barry et al, 2006;Bird et al, 2001;Bonin, Boyer, Méot, Fayol, & Droit, 2004b;Bonin et al, 2003;Bonin, Perret, Méot, Ferrand, & Mermillod, 2008;Cameirão & Vicente, 2010;Cuetos et al, 1999;Cuetos et al, 2012;De Deyne & Storms, 2007;Della Rosa et al, 2010;Dimitropoulou et al, 2009;Johnston, Dent, Humphreys, & Barry, 2010;Lyons et al, 1978;Manoiloff et al, 2010;Marques, Fonseca, Morais, & Pinto, 2007;Moors et al, 2013;Moreno-Martínez et al, 2014;Nishimoto et al, 2005;Nishimoto, Ueda, Miyawaki, Une, & Takahashi, 2012;Raman et al, 2014;Schock, Cortese, Khanna, & Toppi, 2012;Schröder, Gemballa, Ruppin, & Wartenburger, 2011;Sirois et al, 2006;Stration et al, 1975;Tsaparina et al, 2011;Vinson et al, 2008;Walley & Metsala, 1992;Winters, Winter, & Burger, 1978). In the remaining articles, the wording BWhen do you think you learned this word?^is most frequently used (e.g., Auer & Bernstein, 2008;Barca et al, 2002).…”
Section: Methodological Aspects Of Aoa Studiesmentioning
confidence: 99%
“…Up to now, the few norms available have been the recent AoA norms from the works of Marques and colleagues (Marques, Fonseca, Morais, & Pinto, 2007) and Cameirão and Vicente (2010) for 834 and 1,749 Portuguese words, respectively, but based on different data collection procedures (Marques et al, 2007, collected the AoA ratings using a 7-point scale based on Gilhooly and Logie's, 1980, procedure, whereas Cameirão and Vicente used a 9-point scale following Carroll and White's, 1973, work). Subjective norms for valence, arousal, and dominance were also collected for 1,034 words in the recent adaptation of the Affective Norms for English Words (ANEW; Bradley & Lang, 1999) into European Portuguese (Soares, Comesaña, Pinheiro, Simões, & Frade, 2012).…”
mentioning
confidence: 99%
“…It is worth noting that the MWP also integrates words that match those in the abovementioned national (Cameirão & Vicente, 2010;Marques et al, 2007;Soares et al, 2012) and international databases: namely, the Bristol norms of Stadthagen-Gonzalez and Davis (2006)-one of the biggest subjective databases used in research, which provides AoA, imageability, and familiarity norms for 3,394 English words-the recent work of Brysbaert et al (2014), which presents norms of concreteness for 40,000 English lemmas, and the Balota et al (2001) norms, which provide subjective frequency ratings for 2,938 English words. This option allowed us not only to crossvalidate the MWP with its national and international counterparts in which the same and other subjective variables (i.e., familiarity, AoA, valence, arousal, and dominance) are available, but additionally to contribute to a more complete characterization of the Portuguese stimuli typically used in experimental research.…”
mentioning
confidence: 99%
“…A set of six one-word items for training plus 22 oneword items for the acoustic and perceptual test (i.e., experimental condition) were selected, taking into account criteria for high frequency and age of acquisition equal or inferior to 5 years (Cameirão and Vicente, 2010;Gomes and Castro, 2003; the complete list is in Appendix A). The words consisted of food-related items (e.g., laranja, orange) with different lengths in number of syllables (from 1 to 3).…”
Section: Methodsmentioning
confidence: 99%